The Evolution of Nominal Convergence After Accession to The European Union. The Case of Romania - Matei, Elena Florentina; Mindrican, Ioana Manuela (European Journal of Sustainable Development, 2022)
Economic and Monetary Union is the result of progressive economic integration that includes collective regulation for the free movement of goods, services, labor, capital, and products. Economic and Monetary Union presupposes a common currency and market, but also a monetary policy coordinated by the European Central Bank, which has the role of ensuring economic stability. In this context, the countries wishing to join must be prepared to deal with possible economic imbalances, this being possible through the existence of a high level of economic development. Through this paper, we want to identify the evolution of the nominal convergence criteria established by the provisions of the Maastricht Treaty to identify the level of readiness of the Romanian economy for integration into the Economic and Monetary Union.